From Skyrim to Skellige: Fantasy Video Game Music Within a Neo-Mediaevalist Paradigm. Issue 2 (3rd July 2018) - Lamb, Brendan; Smith, Barnabas
Abstract : Situated within similar digital fantasy environments, The Elder Scrolls V: Skyrim and The Witcher 3: Wild Hunt share numerous aspects of design, including geographical formations, architectural design, and cultural indicators. Music cues are also implemented in similar ways in both games, with either layered stems or complete tracks dynamically adapting to the players' actions. While both their non-diegetic scores aim to support landscape and emotion within the gameworld, differing musical approaches see various utilizations of orchestral, vocal, and folk music elements. It is in fact the diegetic music found in each gameworld, predominantly performed by characters throughout the environments, that share the most musical commonalities in approach yet differ vastly in output. This in-game music espouses approximations of fourteenth-century and neo-mediaevalist traditions, but as creations of fantasy these musical endeavours are often historically inaccurate. This presents a compelling musical dichotomy of fantasy tropes and historical depictions, and it is these differing musical approaches that this article aims to explore.